Instinto e civilização: a sociologia processual de Norbert Elias e seu encontro com a psicanálise freudiana - Goiana, Francisco Daniel Iris (2014)
This work make a reflective analysis on the work of the sociologist Norbert Elias, especially in its interpretation of the civilizing process occurred in Europe from the formation of European absolutist states, present in The Civilizing Process (1939). In the constitution of his Sociology, Elias brings an interdisciplinary proposal to sociologically analyze a historical object. For this analysis, the author makes use of freudian psychoanalysis. I tried to make this work, first an analysis sociobiographical Freud and Elias, addressing his intellectual formation, looking for a 'meeting point' of these two authors. Specifically, this site was the Frankfurt School, which had a very strong relationship between social theory and psychoanalysis, which influenced authors such as Herbert Marcuse and Theodor Adorno. In his life, Elias comes into contact with Freud's work during the period he was in the city (1929- 1933), when he was assistant Karl Mannheim. The initial period of Elias in Frankfurt coincides with the release of Civilization and its Discontents, the great work in which Freud, even starting from a clinical assumption makes a great analysis of the social. Elias falls into a tradition of authors who used psychoanalytic theory as support for the construction of both theories in the field of Sociology and Anthropology. So we did a genealogy of this interaction and realize that it occurs almost simultaneously with the emergence of sociology, anthropology and psychoanalysis, with Freud himself one of the authors to make this interaction in works such as Totem and Taboo and Civilization and its Discontents, among others. Based on these works and concepts formulated by Freud to the ideas of 'superego', 'instinctual repression', Elias constructs his theory of the 'civilizing process'. This process, Elias tells us that is mostly based on a repression of affects and emotions process, which in Freud's language is the 'repression of instincts' which leads to the formation of the superego, our moral censor. For Elias this 'repression' occurs in two stages: first through an external coercion, with the emergence of feelings such as shame that path leads to internalization of these prohibitions causing individuals to self-control their emotions, such a rationalization process. When formulated his idea of 'civilizing process', Elias also postulated that this process is not unilinear and is not totally safe thus resulting in the idea of 'descivilizing process' that occur in situations such as wars and genocides and Elias analyzed in its The Germans work.